Optimization of vegetative and in vitro propagation for giant reed (Arundo donax L.) - Tong, Siaw Hoei (2019)
Arundo donax L. or also known as giant cane or giant reed is well known as the source of musical reeds and industrial cellulose. It is potential for phytoextraction of arsenic from synthetic wastewater, and also considered as a promising energy crop due to its high biomass production. It yields three times as much ethanol per acre as corn therefore qualifies it as a cellulosic renewable fuel. This sustainable energy crop for second generation ethanol is also found in Malaysia, but was never known as native nor invasive. The fact that it can grow in Malaysia into full flowering stage brings possibilities that it can be cultivated for biofuel purposes. A. donax L. has been cultivated for biofuel in countries such as Italy but never in Malaysia. Prior to cultivation, their agronomic practices are required. A study was conducted to determine suitable techniques in producing seedlings of A. donax L. for its cultivation. Two methods were approached, vegetative propagation and in vitro propagation. For vegetative propagation, the effects of root hormone, Sadex ® and IBA, at concentration of 0-5 mg L-1 Sadex ®, 0-5 g L-1 Sadex ® and 0-5 mg L-1 IBA respectively were studied on soft and hard wood cuttings. When using hardwood cuttings, cutting should firstly be treated with 1g L-1 Sadex ® for root induction then followed by 4g L-1 Sadex ® for elongation. When using softwood cuttings, 1g L-1 Sadex ® was the optimum concentration. For in vitro propagation, the effects of BAP, IBA, and NAA for multiple shoots induction of A. donax L. were studied. The optimum BAP concentration for shoot regeneration of A. donax L. was 0.2 mg L-1 and optimum IBA was 0.4 mg L-1. Both concentrations resulted with an average of 1.8 shoot per explants. Callus was induced on explant cultured in MS media supplemented 5mg L-1 NAA. This study suggest that vegetative propagation was more economical for seedlings production of Arundo donax L. as the time for shoot regeneration and the number of shoots was similar to those produced in vitro. However, in vitro cultures provide better techniques for mass production of seedlings through indirect callus regenerations. The outcomes of this study were suitable and could be applied for the production of this high potential energy crop.